2016
DOI: 10.4254/wjh.v8.i36.1602
|View full text |Cite
|
Sign up to set email alerts
|

Restructuring of the vascular bed in response to hemodynamic disturbances in portal hypertension

Abstract: In recent years, defined progress has been made in understanding the mechanisms of hemodynamic disturbances occurring in liver cirrhosis, which are based on portal hypertension. In addition to pathophysiological disorders related to endothelial dysfunction, it was revealed: There is the restructuring of the vasculature, which includes vascular remodeling and angiogenesis. In spite of the fact that these changes are the compensatory-adaptive response to the deteriorating conditions of blood circulation, taken t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 52 publications
0
10
0
1
Order By: Relevance
“…6 It has been reported that dozens of factors such as the hemodynamic changes, blood hypercoagulable state, and irrational use of coagulation drugs are associated with PVT. 79 In general, the initial symptoms of PVT are not obvious. It cannot be confirmed by imaging examination at early stage and is easy to be misdiagnosed or missed.…”
Section: Introductionmentioning
confidence: 99%
“…6 It has been reported that dozens of factors such as the hemodynamic changes, blood hypercoagulable state, and irrational use of coagulation drugs are associated with PVT. 79 In general, the initial symptoms of PVT are not obvious. It cannot be confirmed by imaging examination at early stage and is easy to be misdiagnosed or missed.…”
Section: Introductionmentioning
confidence: 99%
“…This leads to PH progression and the occurrence of related complications, particularly variceal bleeding (Figure 1). 3 …”
Section: Pathophysiological Mechanisms Of Portal Hypertension In Livementioning
confidence: 99%
“…These pathophysiological disturbances may be the initial step in the development of portosystemic collateral circulation. 9,10 Detection and Classification of Portal Hypertension PH can be classified into three main categories based on the anatomic location of flow obstruction: prehepatic, intrahepatic, and posthepatic. Intrahepatic PH can be further subdivided into presinusoidal, sinusoidal, and postsinusoidal.…”
Section: Pathophysiologymentioning
confidence: 99%